Enhanced one-photon double ionization of atoms and molecules in an environment of different species - Stumpf, Vasili; Kryzhevoi, Nikolai V.; Gokhberg, Kirill; Cederbaum, Lorenz S. (Physical review letters, 2014)
The correlated nature of electronic states in atoms and molecules is manifested in the simultaneous emission of two electrons after absorption of a single photon close to the respective threshold. Numerous observations in atoms and small molecules demonstrate that the double ionization efficiency close to threshold is rather small. In this Letter we show that this efficiency can be dramatically enhanced in the environment. To be specific, we concentrate on the case where the species in question has one or several He atoms as neighbors. The enhancement is achieved by an indirect process, where a He atom of the environment absorbs a photon and the resulting He+ cation is neutralized fast by a process known as electron transfer mediated decay, producing thereby doubly ionized species. The enhancement of the double ionization is demonstrated in detail for the example of the Mg⋅He cluster. We show that the double ionization cross section of Mg becomes 3 orders of magnitude larger than the respective cross section of the isolated Mg atom. The impact of more neighbors is discussed and the extension to other species and environments is addressed.
Gesehen am 19.08.2020